PENINGKATAN DAYA DUKUNG TANAH URUGAN DENGAN METODE GROUTING DI SMK TEUKU UMAR SEMARANG, JAWA TENGAH - Manalu, Agnes Maria Mutiha (Geological Engineering E-Journal, 2013)
It is very important to note in bearing capacity of soil in development of multi-storey buildings. There are somegeotechnical investigation can do to determine the value of bearing capacity of soil. One of them is cone penetration test.The location of three-storey building site SMK Teuku Umar, Karangrejo, Semarang has soils that dominated by clay.Soil located in the research area is quarry with low soil strength.The purpose of this research was determine the type ofsoil and the bearing capacity of soil in the areas of research, to know grouting method used to increase the strength ofsoil, to determine the bearing capacity of soil before and after grouting, and to know increasing the bearing capacity ofsoil from the work of grouting. The method used in this research is conducting geotechnical investigations in the formcone penetration test. This cone penetration test calculate the value of conus resistance on the subsurface with a certaindepth, then the results of the testing is done processing data to determine the value of bearing capacity of soil containedin the three-storey building site SMK Teuku Umar, Semarang, Central Java. The type of soil in research location isburial land which is dominated by clay to sandy silt. The value of bearing capacity of soil permits at cone penetrationtestâs point 1 before grouting >100 ton/m2 obtained at a depth of 6,4 m. After installing grouting, it found at a depth of3,6 m. At cone penetration testâs point 2, bearing capacity of soil permits before grouting >100 ton/m recentlyrecovered at a depth of 6,6 m. After installing grouting, has been found at a depth of 3,8 m. At cone penetration testâspoint 3, value of bearing capacity of soil permits is increased very high, at depth of 1,6 m has had bearing capacity ofsoil permits >100 ton/m2. Method of grouting has increased the value of bearing capacity of soil. 2